Association of NKAPL rs1635 With Cognitive Function in Early-Onset Schizophrenia - Yang, Yang; Su, Yi; Wei, Guiming; Kang, Zhewei; Lu, Zhe; Liao, Yundan; Lu, Tianlan; Yan, Hao; Yue, Weihua; Qin, Ying; Zhang, Yuyanan (Frontiers in Genetics, 2022)
BACKGROUND: Schizophrenia is a severe mental disorder with high heritability, and cognitive dysfunction is one of the core features. Growing evidence suggests the genetic risk of schizophrenia may contribute to cognitive impairments. The variant rs1635 (nucleotide sequence: c.455C>A; amino acid sequence: T152N) located on the (NFKB activating protein like) NKAPL gene confers risk for schizophrenia and might play a role in the neurodevelopmental process, which is particularly relevant to cognitive function. However, the relationship between rs1635 and cognitive function remains unclear. METHODS: A total of 130 patients with early-onset schizophrenia (EOS) and 300 patients with adult-onset schizophrenia (AOS) of Han Chinese were recruited and underwent neurocognitive tests by using the MATRICS Consensus Cognitive Battery (MCCB). The NKAPL rs1635 was genotyped by using DNA sequencing. The peripheral blood NKAPL mRNA expression level was examined in 152T or 152N carriers (n=20) in EOS patients, by using the quantitative real-time PCR (qRT-PCR). The phosphorylation level of NAKPL T152N polymorphism was detected by cell experiments. In utero electroporation of mouse embryos was examined to explore the effect of Nkapl on neuronal migration. RESULTS: Compared with rs1635 AA and AC carriers, CC, encoding the protein NKAPL-152T, carriers of EOS patients performed better in cognitive domain of processing speed (t = 2.644, P = 0.009), including trail making test (t = 2.221, P = 0.028) and category fluency (t = 2.578, P = 0.011). However, patients with AOS exhibited no significant differences in seven domains among the three genotype groups. In EOS patients, NKAPL mRNA level in NKAPL-152N carriers is significantly lower than that of NKAPL-152T carriers. The phosphorylation level of NKAPL-152N is significantly decreased compared to NKAPL-152T. In utero electroporation showed that Nkapl deletion impairs the embryonic radial migration process. CONCLUSION: The present study found that NKAPL rs1635 was associated with cognitive impairments and peripheral blood mRNA expression level in EOS patients. The NKAPL T152N may affect the NAKPL mRNA expression level and embryonic cortical neuronal migration by regulating the NAKPL protein phosphorylation, which suggested that NKAPL rs1635 might affect cognitive function by regulating early brain development in early-onset schizophrenia.